VALENCY FEATURES OF EMOTIVE VERBS: A COMPARATIVE STUDY OF UZBEK AND ENGLISH - Kurvonbekov Manuchekhr Islomjon ugli (Web of Journals Publishing, 2025)
This article uses a comparative linguistic approach to investigate the valency characteristics of emotive verbs in Uzbek and English. The study focusses on how these verbs' argument form, syntactic behavior, and combinability are affected by their emotional meanings in both languages. The study finds common semantic patterns and language-specific structural variations influenced by grammatical and cultural elements using descriptive and contrastive analyses backed by corpus-based examples. The results have significance for translation studies, lexicography, and language.
Keywords: Emotive verbs, valency, emotive linguistics, comparative analysis, corpus-based analysis.